VARIOUS KINDS of TRADITIONAL CLOTHING INDIAN SOCIETY - Khansa Luthfi Musyaffa; Fajar Prihati; Amin Sulistiyowati (Akademi Seni dan Desain Indonesia Surakarta, 2024)
This journal uses qualitative research methods through document or text studies. It is a study that focuses on the analysis or interpretation of written material based on the context. Materials can be in the form of published notes, books, texts, newspapers, magazines, articles and the like. The data used as a reference for this journal is taken from online journals and digital books, which have previously been reviewed by the author and then summarized and set forth in written form with the title Types of Indigenous Clothing of the Indian Society. India is one of the countries that is very influential in ancient Asian civilizations. Saree from India is one of the oldest clothing in the world. Many fashion clothes are inspired by Indian clothes and applied in a more modern style. Even though there are Western clothing styles that colonized India, India is still able to maintain the Saree as part of the characteristics of the Indian State.